Involvement of specific proteins (Sp1/Sp3) and nuclear factor Y in basal transcription of the distal promoter of the rat pyruvate carboxylase gene in β-cells - Piyanate Sunyakumthorn (2018)
Pyruvate carboxylase plays diverse roles in different biosynthetic pathways, including glucose-induced insulin secretion in pancreatic β-cells. We have localized the control region of the P2 promoter by generating a series of 5′-nested deletion constructs, and both 25- and 9-bp internal deletion constructs, as well as by performing site-directed mutagenesis. Transient transfections of these constructs into INS-1 cells identified a CCAAT box and a GC box that are located at -65/-61 and -48/-41, respectively, as the important determinants. Disruption of the GC box resulted in a 4-fold reduction of the reporter activity, while disruption of the proximal CCAAT box (-65/-61) but not the distal CCAAT box (-95/-91) increased the reporter activity by 3-fold. Simultaneous disruptions of both the GC box and the CCAAT box reduced the reporter activity to a level that was close to that of the single GC box mutation. Electrophoretic mobility shift assays (EMSAs) and supershift EMSAs using nuclear extract from INS-1 cells demonstrated that Sp1 and Sp3 bind a GC box while the nuclear factor Y was shown to bind the proximal but not the distal CCAAT box. © 2005 Elsevier Inc. All rights reserved.